Association of phthalate exposure with all-cause and cause-specific mortality among people with hypertension: The U.S. National Health and Nutrition Examination Survey, 2003–2014. (September 2022) - Yan, Shiwei; Hu, Cong; Wang, Yu; Gao, Jian; Wang, Ziqi; Han, Tianshu; Sun, Changhao; Jiang, Wenbo
Abstract: There is growing evidence that phthalate exposure results in a deteriorated effect on human health, while very few studies directly investigate the relationship of phthalate metabolites with mortality among people with hypertension. We aimed to explore whether exposure to phthalates is associated with all-cause and cause-specific mortality among people with hypertension. This study included 4012 people with hypertension from the National Health and Nutrition Examination Survey from 2003 to 2014. Death information was obtained from the National Death Index until 2015. A total of 577 deaths including 196 deaths due to cardiovascular disease (CVD) and 119 deaths due to cancer were documented. Cox proportional hazards regression models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI). After adjustment for potential covariates, participants exposed to mono-ethyl phthalate (MEP) had a higher risk of cancer mortality (HR, 2.06; 95% CI, 1.07–3.95). Participants exposed to mono-n-butyl phthalate (MnBP) had higher risks of all-cause (HR, 1.83; 95% CI, 1.28–2.60), CVD (HR, 2.19; 95% CI, 1.21–3.95), and cancer (HR, 2.35; 95% CI, 1.07–5.17) mortality. Participants exposed to mono-benzyl phthalate (MBzP) had higher risks of all-cause (HR, 2.19; 95% CI, 1.58–3.05) and CVD (HR, 2.36; 95% CI, 1.35–4.13) mortality. Participants exposed to di-2-ethylhexylphthalate (DEHP) had a higher risk of all-cause mortality (HR, 1.69; 95% CI, 1.19–2.39). Our findings suggested that higher levels of specific phthalates were significantly associated with increased risks of all-cause, CVD, and cancer mortality among people with hypertension. Further studies are needed to confirm these findings and identify the underlying mechanisms. Graphical abstract: Image 1 Highlights: Exposure to phthalates was associated with all-cause, CVD, and cancer mortality among people with hypertension. There exists the positive linear association between phthalates and all-cause, CVD, and cancer mortality. Further studies are needed to confirm the findings and identify mechanisms.